Sifat Kuantitatif Burung Weris (Gallirallus philippensis) Jantan dan Betina - Fahrijal Moyiu; Fahria Datau; Safriyanto Dako; Suparmin Fathan (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2020)
The purpose of this study was to determine the quantitative nature of male and female Weris (Gallirallus philippensis) in Wonosari District, Boalemo Regency. The study was conducted in August-October 2019. This study used a sample of 20 Weris birds consisting of 10 males and 10 females. The method used is a survey method, through direct observation in the field. Observations on the quantitative nature of Weris birds (Gallirallus philippensis) were carried out directly at the research location. The data obtained were analyzed descriptively. The results showed the average body size of male Weris birds were: body weight 171.9 gr, femur length 5.42 cm, tibia length 6.81 cm, long shank 4.56 cm, third finger length 3.48 cm, maxilla length 3, 14 cm, wing length 11.20 cm, neck bone length 7.07 cm, shank circumference 1.68 cm. Body weight of male weris 171.9 ± 11.06, females 135.90 ± 11.82 with diversity coefficient 6.43 and 8.70